Tinjauan Yuridis Mengenai Kejahatan Pedofilia Berdasarkan Hukum Pidana Di Indonesia Dan Hukum Pidana Di Australia - jprautor, jprautor (JURNAL PROPERTY RIGHTS, 2015)
Pedophilia is one of sexual violence crime to children. Performer pedophilia is adults that have deviate sexual behavior to children. The establishment of criminal law especially about pedophilia crimes is need to be reviewed more serious with criminal law comparison between civil Law country as Indonesia and common law country as Australia.Based on that, this research take the problems, that ere, how is the law settingup for pedophilia crime based on criminal law Indonesia, how is the law setting up for pedophilia crime based on criminal law in Australia, and how is the comparison of criminal law setting up for pedophilia creme performer in Indonesia and Australia. The purpose of this research is to knowing and analyzing about law comparison of pedophilia crime based on criminal law in Indonesia and Australia. The benefit is to give knowledge about law comparison of pedophilia crime based on criminal law in Indonesia and Australia.The research type in this thesis is normative juridical law research that used legislation approach method and conceptual approach method. The kind of law material was got from primary, secondary, tertiary law material and then being analyzed using inductive deductive analysis technique.Based on the analysis of the reseach and discussant with method above, can be concluding that. Law the comparison about pedophilia crime based on criminal law in Indonesia and Criminal law in Australia , in Indonesia has been regulated in KUHP law (KitabUndang-Undang Hukum Pidana) chapter XIV book II, morality crime section 289 to 296 and constitution No.23 year 2002 about children protection chapter XII section 81,82, and 88. While in Australia has been regulated on Criminal Code 1995 chapter 8âoffences against humanity and relates offencesâ on sectin 268.59 paragraph 1-6 and also in Criminal Code Amandemen (Slavery and Sexual Servitude ) Act 1999 Chapter 8âoffences againt humanity, division 270 . And it can be concluded that punishment for pedophilia concluded that punishment for pedophilia crime performer is heavier in Australia according to Criminal Code 1995 that is imprisonment for 25 year, and according to Criminal code amendemen (Slavery and Sexual Servitude) Act 1999 that punishment jail for 19 years and Sexual Act For Child 15 years. While is pedophilia crime performent according to KUHP section 292 in Indonesia is imprisonment maximum 5 years and according to constitution no.23 year 2002 about children protection section 82 is imprisonment maximum 15 years and minimum 3 years and fine maximum three hundres million rupiahs and minimum sixty million rupiah.